La inserción laboral de individuos rehabilitados post-condena en el Ecuador. - León Castelo Jennifer Andrea (2025)
The post-conviction life of an individual is extremely unstable, essentially in the labor field, since there are few possibilities for an ex-convict to be interest to those who need to fill a job position. Ecuador is going through a critical prison crisis, as a result of the lack of rehabilitation of those serving a sentence. There are currently 32.360 men and women in prison, and there is no exact number of those who have been rehabilitated and subsequently reintegrated into society, specifically in the labor market. This research focuses on the possibility of inserting these individuals into the labor market, whit the objective of identifying public policies and determining programs that facilitate the reintegration of ex-convicts. For the development of this project it is necessary to use a mixed methodology, which allows the inclusion of quantitative and qualitative data that facilitate the analysis of the most relevant aspects that justify this research. Keywords: Labor market insertion, post-conviction individuals, rehabilitation.